The Application of Mesoporous Silica Nanoparticles in Enhancing the Efficacy of Anti-Atherosclerosis Therapies: A Review - Budiman A; Mutmainah L; Anjelina M; Fitriawati MK; Pilihanto EI; Amaliah S; Aulifa DL (International Journal of Nanomedicine)
Arif Budiman,1 Luthfiyyah Mutmainah,1 Martina Anjelina,1 Mila Karisma Fitriawati,1 Eufrasia Ine Pilihanto,1 Salma Amaliah,1 Diah Lia Aulifa2 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Arif Budiman, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang Km. 21, Bandung, 45363, Indonesia, Email arif.budiman@unpad.ac.idAbstract: Atherosclerosis (AS) is a chronic inflammatory condition of large arteries and a major contributor to cardiovascular disease (CVD) and stroke. The prevention of AS diseases involves numerous anti-atherosclerosis agents, including antihyperlipidemic and antihypertensive drugs. However, these drugs often exhibit poor aqueous solubility, which can affect their bioavailability and therapeutic efficacy. Mesoporous silica nanoparticles (MSNs) have emerged as effective drug delivery systems due to their high surface area, tunable pore sizes, surface functionalization potential, and physicochemical stability. These characteristics enable enhanced drug loading, regulated release, and stabilization of amorphous drug forms, thereby improving solubility, permeability, pharmacokinetics, and therapeutic efficacy. This review offers an in-depth look at MSN-based strategies for optimizing the delivery of anti-atherosclerosis drugs, particularly those targeting cholesterol levels and blood pressure control. Relevant data were sourced from PubMed, Scopus, and Google Scholar using the keywords “mesoporous silica nanoparticle”, “atherosclerosis”, “antihyperlipidemic”, and “antihypertensive.” Numerous studies have demonstrated the ability of MSN formulations to significantly enhance drug performance, with reported enhancements in solubility and bioavailability ranging from 1.4-fold to 88-fold, depending on the drug and formulation. For example, nifedipine-loaded MSNs showed an 88-fold increase in solubility compared to the pure drug and a 10-fold improvement over marketed tablets. Simvastatin-loaded MSNs achieved a 6.1-fold enhancement in oral bioavailability, while efonidipine-loaded MSNs exhibited up to a 3.5-fold increase in dissolution and permeability. These advancements may result in decreased dosing frequencies, reduced drug dosages, and fewer adverse effects, ultimately improving patient compliance. However, clinical translation remains limited due to the lack of early-phase clinical trials, insufficient long-term safety data, and challenges associated with large-scale MSN manufacturing. This review highlights the therapeutic potential of MSNs in cardiovascular applications and points out that it requires further research to address translational barriers. With continued development, MSN-based delivery systems hold strong potential to enhance the clinical effectiveness of anti-atherosclerosis therapies.Keywords: atherosclerosis, mesoporous silica, antihyperlipidemic, antihypertensive, bioavailability